Facilitating faculty competency to integrate genomics into nursing curriculum within a private US University - Bashore LM (Dove Medical Press, 2018)
Lisa M Bashore, Glenda Daniels, Lori Borchers, Lynette L Howington, Dennis J Cheek Harris College of Nursing and Health Sciences, Texas Christian University, Fort Worth, TX, USA Background: This quasi-experimental study explored full-time nurse faculty competency in genomics and genetics using a validated measure prior to and following educational sessions during one academic semester. The findings represent the researchers’ efforts to educate nurse faculty and to support their competency in genomics and genetics as information shared with students is only as robust as faculty knowledge.Methods: Faculty who consented to participate completed the Genomic Nurse Concept Inventory (GNCI©) to measure their knowledge of the concepts surrounding genomics and genetics prior to the education intervention and then following all three education sessions. The education sessions were carried out over a semester using a lunch and learn forum.Results: Our first assumption was that 50% of faculty would score below 70% on the pretest. Eligible nurse faculty 29/48 (60%) completed the GNCI© and scores show they had limited knowledge in three areas: nomenclature of genes and gene function, inheritance patterns, and the clinical application of genomics to human disease. Over half of nurse faculty 17/29 (59%) scored less than 70% on the GNCI© supporting our first assumption. The second assumption that over 85% of faculty would score at least 70% on the GNCI© after the education was not supported. The education sessions improved scores on the GNCI© in the 12/29 (41%) faculty who completed the measures prior to and after the intervention.Conclusion: Despite the growing knowledge about genomics/genetics and the application to clinical practice, health professionals like nurses are not competent in these concepts. Nursing faculty require competency in genomics and genetics in order to integrate these concepts in nursing curricula. Outcomes of this project show the need to provide education and support for nurse faculty in genomics and genetics. Keywords: education, genetics, genomics, incorporation, knowledge, undergraduate bachelors program